Pengaruh Kualitas Produk dan Digital Marketing Terhadap Keputusan Pembelian Dengan Emosi Konsumen Sebagai Variabel InItervening (Studi Kasus Pada Wanita Pengguna Platfrom TikTok) - Khair, Hazmanan; Maulidah, Sri Ayu; Pasaribu, Fajar (Journal of Student Development Informatics Management (JoSDIM), 2023)
Purchasing decision is an action or consumer behavior so whether or not to make a purchase or transaction, whether or not the number of consumers in making decisions is one of the determinants of whether or not the company's goals are achieved. In theory, the lower the price of an item, the more demand for the item and the better the quality, the higher the price. The formulation of the problems of this research are: (1) Is there an effect of product quality on purchasing decisions for consumers who use the Tiktok platform?, (2) Is there any influence of digital marketing on purchasing decisions for consumers who use the Tiktok platform?, (3) Is there an effect on quality? Products on consumer emotions on consumers using the Tiktok Platform?, (4) Is there any effect of digital marketing on consumer emotions on consumers using the Tiktok Platform?, (5) Is there an influence of consumer emotions on Purchase Decisions for consumers using the Tiktok Platform?, (6) Is there an effect of product quality on purchasing decisions with consumer emotions as an intervening variable for consumers using the Tiktok platform?, (7) Is there an effect of digital marketing on purchasing decisions with consumer emotions as an intervening variable for consumers using the Tiktok platform?. This study was designed using quantitative methods with a sample size of 356 respondents using Accidental Sampling. The data collection instruments used were questionnaires and documentation. The results showed that (1) Product quality has a significant positive effect on purchasing decisions, (2) Product quality has no significant positive effect on consumer emotions, (3) Digital marketing has a significant positive effect on purchasing decisions , (4) Digital marketing has a significant positive effect on consumer emotions, (5) Consumer emotions have a significant positive effect on purchasing decisions, (6) Product quality has a significant positive effect on purchasing decisions with consumer emotions as a mediating variable, (7) Product quality has no effect significant positive effect on purchasing decisions with consumer emotions as a mediating variable.